Małe dzieci w chrześcijańskiej epigrafice miasta Rzymu i w nauczaniu Jana Chryzostoma - Stawoska-Jundziłł, Bożena (Vox Patrum, 2009)
The paper presents the results of studies of epitaphs for children up to almost eight years of age from the city of Rome (3rd-4th c. – B. Stawoska-Jundziłł, Vixit cum parentibus. Children aged under seven in Christian families from Rome of 3rd-4th c., Bydgoszcz 2008) in comparison with the views of John Chrysostom on the upbringing of small children. The content of over 2000 children from Rome demonstrates a high status of even the youngest offspring in the Christian families from this city. The founders cared for their religious „endowment”, bestowed their love on them and tried to remember them as members of the family even if they had died after a few days or months. It was unquestionably believed that small children are immediately saved, go to God and commune with the saints. Thanks to this the family could hope for their support and prayers. Whereas, John Chrysostom only casually mentions small children and, what is more, ambivalently: on one hand presenting them on the basis of thorough observations of their behavior and looking after them and on the other hand as mindless creatures, a harbinger of valuable person following the Stoics e.g. Seneca. As far as the most important for me question of the death of small children is concerned he takes a stand similar to that of the Romans. The children are really without sins (they did not commit them consciously) so God shall accept them only through the hardships of illness and death. Now they are asleep (unlike in the studied epitaphs) but they will rise from the dead and join their parents. Thus, the despair after their death is pointless; God decided the best for them. The difference lies in the fact that the founders of epitaphs more decidedly see the perfection of posthumous existence of even the smallest children who there reach their full maturity whereas John does not seem to be interested in this issue since he directs his teaching mostly to maturing and mature Christians in the earthly life and not in the beyond.